What makes a European in Scotland?. Issue 2 (May 2019) - McCrone, David
Abstract : Why, if few people in Scotland give priority to being 'European', vis-à-vis being 'Scottish' or being 'British', did a significant majority vote Remain in the 2016 Brexit referendum? Much depends on how questions on territorial identities are asked in surveys. Employing a 7-point scale ranging from 'weakly European' to 'strongly European' we find that as many as 45% put themselves at the strongly European end of the scale in Scotland. Furthermore, and contrary to expectations, being European correlates more strongly with being British than with being Scottish north of the border. Using linear regression analysis, four variables contribute significantly to being strongly European: having liberal ('libertarian') values, high levels of education, supporting the SNP and Independence, and feeling 'British'. Being 'Scottish' has lesser effect because it is ubiquitous across the social spectrum, and, in any case, national identity in Scotland, in contrast with England, did not account significantly for the 2016 Brexit vote in Scotland. There is evidence, however, that, post-Brexit, being 'European' has taken on more political-constitutional meanings, even though the binary divide between Remain and Leave does not properly reflect the range of policy preferences people adopt concerning the European Union.